Serum Homocysteine and Folic Acid Levels as Risk Factors of Chronic Kidney Disease - Esa Loyallita LESTARI; Nyoman Suci WIDYASTITI; Meita HENDRIANINGTYAS; Muji RAHAYU; Banundari RACHMAWATI (Modern Medicine)
Chronic kidney disease (CKD) is a worldwide health problem. Homocysteine (Hcy) and folic acid (FA) have been found to correlate with intra-renal atherosclerosis, which leads to decreased renal perfusion pressure and may impair the endothelial function of renal arterioles and glomerular capillaries, thus being considered as new risk factors for CKD. Objective: To investigate serum Hcy and FA as risk factors for CKD. Methods: A cross-sectional study was conducted on 80 patients who underwent creatinine examination. Hcy and FA levels were examined using enzyme-linked immunosorbent assay (ELISA) method. Bivariate analysis to calculate the prevalence ratio (PR) using a 2x2 table and using Receiver Operating Characteristic (ROC) curves to determine the cut off value of HCY and FA in CKD. Results: The mean Hcy level of CKD patients was 7.66±4.25 µmol/L and without CKD was 4.29 ± 2.71 µmol/L. The mean FA levels of CKD and non-CKD patients were 6.75±1.75 and 9.27±9.28 ng/mL, respectively. The prevalence ratio of Hcy to CKD was 2.17 (95%CI=1.35-3.45; p=0.001). The prevalence ratio of FA to CKD was 1.75 (95%CI=1.11-2.75; p 0.014). Conclusion: Increased Hcy levels and decreased serum FA levels are risk factors for CKD.